Exploring the intersection of structural racism and ageism in healthcare. Issue 12 (10th November 2022) - Farrell, Timothy W.; Hung, William W.; Unroe, Kathleen T.; Brown, Teneille R.; Furman, Christian D.; Jih, Jane; Karani, Reena; Mulhausen, Paul; Nápoles, Anna María; Nnodim, Joseph O.; Upchurch, Gina; Whittaker, Chanel F.; et al.
Abstract: The American Geriatrics Society (AGS) has consistently advocated for a healthcare system that meets the needs of older adults, including addressing impacts of ageism in healthcare. The intersection of structural racism and ageism compounds the disadvantage experienced by historically marginalized communities. Structural racism and ageism have long been ingrained in all aspects of US society, including healthcare. This intersection exacerbates disparities in social determinants of health, including poor access to healthcare and poor outcomes. These deeply rooted societal injustices have been brought to the forefront of the collective public consciousness at different points throughout history. The COVID‐19 pandemic laid bare and exacerbated existing inequities inflicted on historically marginalized communities. Ageist rhetoric and policies during the COVID‐19 pandemic further marginalized older adults. Although the detrimental impact of structural racism on health has been well‐documented in the literature, generative research on the intersection of structural racism and ageism is limited. The AGS is working to identify and dismantle the healthcare structures that create and perpetuate these combined injustices and, in so doing, create a more just US healthcare system. This paper is intended to provide an overview of important frameworks and guide future efforts to both identify and eliminate bias within healthcare delivery systems and health professions training with a particular focus on the intersection of structural racism and ageism.